Interventional Ultrasound in Dermatology: A Pictorial Overview Focusing on Cutaneous Melanoma Patients - Corvino, Antonio; Catalano, Fabio; Cipolletta Campanile, Anna; Cocco, Giulio; Delli Pizzi, Andrea; Corvino, Fabio; Varelli, Carlo; Catalano, Orlando (Journal of ultrasound in medicine, 2022)
Cutaneous melanoma incidence is increasing worldwide, representing an aggressive tumor when evolving to the metastatic phase. High‐resolution ultrasound (US) is playing a growing role in the assessment of newly diagnosed melanoma cases, in the locoregional staging prior to the sentinel lymph‐node biopsy procedure, and in the melanoma patient follow‐up. Additionally, US may guide a number of percutaneous procedures in the melanoma patients, encompassing diagnostic and therapeutic modalities. These include fine needle cytology, core biopsy, placement of presurgical guidewires, aspiration of lymphoceles and seromas, and electrochemotherapy.